Silterra cleaning solution in post chemical mechanical polishing oxide to minimize ammoniacal nitrogen in effluent - Said, Muhammad Asyraf (2023)
Malaysia’s Department of Environment (DOE) has introduced ammoniacal nitrogen as a new parameter to be regulated under the Environment Quality (Industrial Effluents) Act effective from 1st January 2010. The penalty for not complying to any provision of the Environmental Quality Act (EQA) is a fine not exceeding RM10,000 and/or up to two years imprisonment with an additional fine of RM1,000 per day so long as the offence continues. Extensive use of ammonium hydroxide particularly in the Chemical Mechanical Polishing (CMP) process has been identified as one of the contributing factors that led to the high ammoniacal nitrogen in the final discharge. This thesis focuses on evaluating the Scrubbing cleaning efficiency using a SpeedFam IPEC (SFI) AvantGaard™ 776 polisher at CMP as high flow of effluents containing ammoniacal nitrogen is being discharged due to the rinsing of ammonium hydroxide flow mixed with ultra pure water (UPW). The main objective of this study is to formulate an alternative cleaning process at the Scrubbing stage without compromising the cleaning efficiency. The unique formulation of SCS (SilTerra Cleaning Solution) containing hydrogen peroxide, sulphuric acid and an additive has been analyzed in the Scrubbing process since it contains the necessary ingredients to oxidize and dissolve the contaminants on wafers surface. The formulated acid provides comparable capability with ammonium hydroxide on particles and metallic ions in which both cations and anions removal efficiency was higher than 97%. The chemical is a proprietary of SilTerra by four inventors registered as a trade secret invention. It was discovered that the particles on the wafers were effectively removed with 99% efficiency during the Buffing step. The attempt to eliminate the application of chemicals during Scrubbing requires further studies as the Sulphur removal was not promising with the removal efficiency lower than 84%, comparatively lower than SCS and ammonia, delivering more than 97% removal. It is generally known that mobile ions especially the metallic residuals may damage the circuits but the allowable limit of mobile anions affecting post-CMP processed wafers were not discussed in details. In addition to this, these anions are expected to be cleaned by Tungsten slurry applied during Buffing process which is acidic and contains more than 3% hydrogen peroxide. As such, application of chemical solution during Scrubbing process is considered as a redundant process. The redundancy of the second stage of post-CMP cleaning, Scrubbing, has led to the opportunity of improving the CMP SFI equipment capacity particularly for the oxide process at 15%.